The Relevance of Ibnu Qayyim Al-Jawziyyah’s Moral Education to The Moral Crisis of Modern - Zulfahmi; Agustianda; An Nu’man; Benny Prasetiya (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
The moral crisis among modern students has become one of the major challenges in contemporary Islamic education. The development of digital technology, globalization, and socio-cultural transformation has significantly influenced the behavior of younger generations, resulting in various forms of moral degradation such as declining ethics, weak self-control, individualistic attitudes, and decreasing respect for social and religious values. This condition indicates that modern education tends to emphasize cognitive achievement rather than moral character formation. This study aims to analyze the concept of moral education according to Ibn Qayyim al-Jawziyya and examine its relevance to the moral crisis of modern students. This research employs a qualitative approach based on library research using content analysis and contextual hermeneutic methods. Primary data were obtained from the works of Ibn Qayyim al-Jawziyyah, while secondary data were collected from scientific journals, academic books, and relevant previous studies. The findings reveal that Ibn Qayyim al-Jawziyyah’s concept of moral education emphasizes the importance of tazkiyat al-nafs (self-purification), self-control, exemplary behavior, and spiritual development as the foundation of character formation. These concepts are highly relevant in addressing the moral problems of modern students because they integrate spiritual, moral, and intellectual dimensions within the educational process. This study implies the importance of strengthening character education based on spiritual values in the contemporary Islamic education system